Preoperative neck ultrasound combined with pathological data can significantly impact the outcome of medullary thyroid carcinoma - Maurilio Deandrea; Tommaso Piticchio; Alberto Mormile; Francesca Retta; Giovanni Canale; Alessandra Caracciolo; Lorenzo Daniele; Pierpaolo Trimboli (Endocrine Journal)
The diagnosis of medullary thyroid carcinoma (MTC) is challenging since the accuracy of ultrasound (US) and fine-needle aspiration cytology are suboptimal. As a result, MTC has a generally poor prognosis. The aim of this study was to analyze whether perioperative data can modify the risk of relapse in these patients. The institutional database of Turin Mauriziano Hospital was searched to extract records of MTCs diagnosed between 2000 and 2021. Kaplan-Meier curves and Cox and logistic regression analyses were performed, and the hazard ratio (HR) was calculated. Seventy-three MTC patients (median age 58 yr) were found. Disease-free survival was significantly different according to staging (HR: 9.12; p = 0.037), capsular status (HR: 5.49; p = 0.02), and neck US (HR: 9.19; p = 0.04). In the logistic regression analysis, CEA level (β: –0.01; p = 0.043), histological multifocality (OR: 7.4; p = 0.034), and metastatic lymph nodes at histology (β: –0.13; p = 0.006) were significantly associated with structural recurrence. Two logistic multivariate models best explained the variance in recurrence: 1) neck US presentation plus histological multifocality (AIC: 27; r2: 0.37; x2: 12.4; p = 0.002) and 2) number of neck metastases plus capsular invasion (AIC: 26; r2: 0.40; x2: 13.7; p = 0.001). Pathological data are associated with MTC prognosis. Preoperative neck US can significantly help to predict MTC outcome.